Towards enhanced photovoltaic Modeling: New single diode Model variants with nonlinear ideality factor dependence - Martin Ćalasan; Snežana Vujošević; Gojko Krunić (Engineering Science and Technology, an International Journal)
The energy sector is increasingly challenged to transition to sustainable and renewable energy sources. Solar cells play a pivotal role in this process, enabling the direct conversion of solar energy into electricity. Traditional solar cell models, such as the single-diode model (SDM), often assume a constant diode ideality factor, despite research indicating its dependence on voltage. This study introduces five novel SDM variants that incorporate the nonlinear dependence of the diode ideality factor on voltage, aiming to improve the accuracy of current–voltage (I-V) characteristic modeling. For each of the proposed models, an analytical current–voltage relationship was derived using the Lambert W function, ensuring precise representation of the system’s behavior. Experimental validation was conducted on a standard solar cell (RTC France) and three commercial modules (MSX60, PWP201, KC200GT), demonstrating significant reductions in modeling errors (RMSE) compared to classical SDM, DDM, and TDM approaches. Furthermore, the analysis highlights the stable performance of the proposed models under varying conditions of insolation and temperature, confirming their robustness and practical applicability. This work provides an innovative framework for enhancing solar cell modeling, laying the foundation for future research and practical applications in optimizing photovoltaic systems.